A telephelyválasztás aktuális kérdései - Veres, Lajos (Közép-Európai Közlemények, 2017)
With the penetration of globalization the expansion of multinational companies crosses national borders. Many of the traditional location selection factors lose their significance, simultaneously the value of other factors may increase, and this process shows variable specificities in time and space. As a result of the movement of population a major social process can be seen in the increase of urban population, through which city development steps into another phase. As a result of the suburbanization the growing and more expansive cities and city regions become attracting for market players. Market supplier companies face decisions concerning the selection of a new location or the optimalization of an already existing location structure of distribution network. The study overviews the major economic trends of globalization, and the major aspects of company location selection processes and the same time discussing some of the successfully applicable decision making methods.